Predictive value of combined inflammatory markers for septic cardiomyopathy: a retrospective study - Xianqi Lan; Huiqiang Mai (BMC Infectious Diseases)
Abstract Background Septic cardiomyopathy (SCM) is a common but underdiagnosed complication of sepsis characterized by acute myocardial dysfunction driven by inflammatory and immune dysregulation. This study aimed to investigate the clinical characteristics, inflammatory profiles, and predictive markers associated with SCM, highlighting its diagnostic and prognostic importance. Methods Clinical data from 89 controls and 71 SCM patients were retrospectively analyzed from January 2022 to July 2024. The differences in demographics, clinical characteristics, hematological parameters, inflammatory markers, and cardiac injury markers were compared between the two groups. Additionally, the risk factors for SCM were evaluated via univariate and multivariate logistic regression analyses. After that, the predictive capacity of each marker for SCM was assessed through the receiver operating characteristics curve analysis. Results The SCM group had significantly higher levels of SOFA score, platelet-to-lymphocyte ratio (PLR), cardiac troponin I (cTnI), neutrophil-to-lymphocyte ratio (NLR), systemic immune-inflammation index, NT-proBNP, and inflammatory markers such as CRP, TNF-α, PCT, and IL-6 (P < 0.05). Multivariate analysis revealed that cTnI (OR = 4.548, 95% CI: 1.164–19.452, P = 0.041), NLR (OR = 4.231, 95% CI: 2.443–7.328, P < 0.001), and CRP (OR = 1.138, 95% CI: 1.061–1.221, P < 0.001) were independent risk factors for SCM. The combined use of NLR, PLR, and CRP yielded an AUC of 0.962, with a sensitivity of 91.5% and specificity of 93.3%. Conclusions SCM is associated with pronounced inflammatory activation and myocardial injury. This study identifies cTnI, NLR, and CRP as independent risk factors. Notably, the combined use of NLR, CRP, and PLR significantly enhances diagnostic accuracy, providing a reliable basis for early identification and targeted intervention in SCM.